Treatment Approach and Outcomes of Vaginal Melanoma. Issue 8 (1st October 2013) - Kirschner, Austin N.; Kidd, Elizabeth A.; DeWees, Todd; Perkins, Stephanie M.
Abstract : Objective: To describe the characteristics of primary vaginal melanoma patients in the Surveillance, Epidemiology, and End Result database and to determine the outcome from the treatment approaches. Materials/Methods: From the Surveillance, Epidemiology, and End Result registry, 201 patients with vaginal melanoma were identified. Patients' characteristics and prognostic factors including age, race, extent of surgery, and use of radiation therapy were obtained. Results: The median age was 68 years (range, 28–100 years). The population was 73% white, 11% black, and 16% Asian/American Indian. International Federation of Gynecology and Obstetrics staging results were stage I (46%), stage II (18%), stage III (3%), stage IVA (3%), stage IVB (12%), and unknown (18%). Treatment approach included surgical resection of the primary site in 70%, whereas 35% of the patients underwent lymph node resection. Approximately 40% of the patients received radiotherapy, which was primarily used in the adjuvant setting. Overall survival at 2 and 5 years was 24% and 15%, respectively. Presence of lymph nodes at diagnosis was associated with worse overall survival (hazard ratio, 1.98; P = 0.02). Adjuvant radiation did not offer a statistically significant overall survival advantage compared to surgery alone. Conclusions: Vaginal melanoma is a rare diagnosis primarily affecting the elderly. Overall survival is low even for patients presenting with disease limited to the vagina. Lymph node involvement at diagnosis is strongly predictive of worse overall survival. Most patients are treated with surgical resection with varying use of adjuvant radiotherapy. Further research is needed to identify the etiology and improve the outcome of this aggressive disease.